2017
DOI: 10.1515/prilozi-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression, Anxiety and Insomnia in Chronic Kidney Disease Patients and their Co-Relation with the Demographic Variables

Abstract: Background: Chronic kidney disease (CKD) is an emerging health problem in both developed and developing countries. Depression, anxiety and sleep disturbances are highly prevalent in patients with chronic disease, but remain undertreated despite significant negative consequences on patients' health. Assessment of key components of mental health early in disease course will help to identify high risk subjects in whom modifying these predictors will help in providing active and healthy life in CKD patients. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 27 publications
6
37
3
1
Order By: Relevance
“…Regarding the indications of depression, more than half of the patients had symptoms, which is in line with the results of a study in India (26) . Depressive disorders in this population can be related to the worst clinical outcomes, comorbidities, complications of the disease and treatment, hospitalizations, increased length of hospital stay, abandonment of dialysis, mortality and reduced quality of life (9,27) .…”
Section: Although the Relationship Between Depressionsupporting
confidence: 88%
“…Regarding the indications of depression, more than half of the patients had symptoms, which is in line with the results of a study in India (26) . Depressive disorders in this population can be related to the worst clinical outcomes, comorbidities, complications of the disease and treatment, hospitalizations, increased length of hospital stay, abandonment of dialysis, mortality and reduced quality of life (9,27) .…”
Section: Although the Relationship Between Depressionsupporting
confidence: 88%
“…Also, depression was more observed in unemployed patients either not working before dialysis or stopped working after dialysis. These results come in agreement with a study done by Aggarwal et al [22], which was a cross-sectional study done on 200 patients of CKD stage III to stage V with dialysis and revealed that depression was significantly correlated to unemployment and low education. On the other hand, our findings disagree with those of Kumar et al [17], who showed that there was no significant relationship between depression and educational level or occupational state.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, a worsening CKD is directly associated with worsened insomnia [6]. Furthermore, a descriptive study published by Aggarwal et al [7] observed insomnia among 60% of patients who underwent hemodialysis (HD), whereas other studies report the frequency of insomnia as 86.5% [8] and 45% [9].…”
Section: Introductionmentioning
confidence: 99%